Scaling in social enterprises: The case of digital social innovations - Ozman, Müge; Gossart, Cédric (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
While a significant body of research examines how offline social enterprises scale social impact, research on scaling in the case of digital social innovations is limited. This is an important issue to address because digital social enterprises have different resources at their disposal, which may facilitate or hinder various scaling strategies used by social enterprises. Distinguishing between three scaling strategies (scaling out, scaling up, scaling deep), we develop indicators to account for scaling in digital social enterprises. Using these indicators, we carry out a clustering analysis on a dataset composed of 189 civic engagement platforms in Europe. Our research reveals three types of platforms in terms of their scaling orientations, which are grassroots, technology provision, and data-based.